Spiritual Leadership as an Antidote to Academic Burnout: A Conceptual Synthesis of Role Conflict Resolution in Islamic Educational Institutions - Fathorrohman; Ahmad Silmul Fuady (DAAR EL-IDARAH: Journal of Islamic Education Management, 2026)
Academic burnout within Islamic higher education has evolved into a systemic psychosocial crisis driven by the intensification of global performativity regimes, where publication metrics, accreditation demands, and bureaucratic accountability structures generate persistent role conflict and ontological dissonance among academics whose professional identity is simultaneously anchored in moral, pedagogical, and spiritual responsibilities. Addressing this condition requires more than managerial adaptation; it necessitates a reconstruction of leadership itself. Employing a Critical Conceptual Synthesis design, this study undertakes a dialectical interrogation of dominant techno-managerial paradigms and systematically reconfigures Fry’s Spiritual Leadership framework as an alternative explanatory and organizational architecture. The synthesis identifies three principal role-conflict typologies idealism–pragmatism incongruence, temporal overload, and ambiguity of rewards and demonstrates that the integrated operationalization of Vision, Hope/Faith, and Altruistic Love functions as a structural mechanism capable of neutralizing Rizzo’s role conflicts while simultaneously mitigating Maslach’s dimensions of emotional exhaustion, depersonalization, and reduced professional accomplishment. The resulting framework advances a paradigmatic shift in Islamic Educational Management, repositioning institutional governance beyond secular corporate mimicry toward an ethical-spiritual model that prioritizes meaning, psychosocial resilience, communal belonging, and human flourishing as foundational conditions of sustainable academic life.